Przepływy między jeziorem Jamno i Bałtykiem w wybranych sezonach letnio-jesiennych lat 1978-2010 - Choiński, Adam (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2016)
This paper presents the results of measurements of discharges in the Nurt Jamneński canal connecting Lake Jamno and the Baltic Sea. The measurements were performed between June and September in various years between 1978 and 2010. The discharges were measured by means of a current meter, and their values were determined by means of the Culmann method or the calculation method. The obtained results are considerably varied, i.e. discharges from the lake to the sea were observed, as well as from the sea to the lake, and lack thereof as a result of a blocked mouth of the Nurt Jamneński canal to the sea. The maximum calculated discharges amounted to several tens of m3s–1. The specificity of the connection of the lake with the sea permitted to show the considerable dynamics of the environment. This manifests itself in the rapid changes of the discharges (even at a daily rate) and frequent transformations of the Nurt Jamneński canal.
Keywords: Nurt Jamneński canal; lake-sea discharges